BAHASA FIGURATIF PADA PUISI “HARAPAN” KARYA IKA MUSTIKA - Armita, Eni (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
This article discusses the figurative language of Ika Mustika's poem "Harapan". The figurative language framework discussed in this article refers to several problems, namely: 1) how is the structure of figurative language used in the poem "Harapan" by Ika Mustika?; and 2) What is the meaning resulting from the use of figurative language?. The method used in this article is qualitative research by focusing on figurative language theories, namely by analyzing the use of figurative language and the meaning produced by it. The results of this study showed that the dominant figurative language in the poem "Harapan" by Ika Mustika is the use of metaphorical majas, which is one of the figurative languages that compares two things in different forms. Thus, this article is expected to contribute theory on the application of the use of figurative language on literary works in the form of poetry so that it can be produced the meaning contained in it.